Last mile mobile hybrid optical wireless access network routing enhancement - Adam Wong Yoon Khang; Shamsul J. Elias; J. Pusppanathan; Nadiatulhuda Zulkifli; N. H. Halim; Shapina Abdullah (Institute of Advanced Engineering and Science, 2019)
This study focuses on mobile ad hoc networks (MANETs) that support Internet routing protocol imposing stringent resource consumption constraints of Quality of service (QoS). The mobile Internet causes the on-going issue of inefficient use of the MANET resources due to its random nature of wireless environments. In this paper, the new improved architecture of the last mile mobile hybrid optical-wireless access network (adLMMHOWAN) is proposed and designed to tackle the arised issues. The proposed design is based on a unified wireless-wired network solution required the deployment of MANET-based wireless fidelity (WiFi) technology at the wireless front-end and wavelengths division multiplexing passive optical network (WDM PON) at the optical backhaul. The critical performance metrics such as network capacity and energy consumption based on modified AODVUU routing protocol using OMNeT++ software is analyzed with 2 scenarios, namely the number of nodes and mobility speed. This mode of communication results in better QoS network capacity of 47.07% improvement, with 26.85% reduction of lower energy resource consumption for mobile wireless front-end over passive optical network backhaul architecture when compared with the existing work of oRiq scheme that focus on improvement in MANETs.